METHOD OF SOLVING THE PROBLEM OF SITUATIONAL MANAGEMENT OF THE SEMANTIC KERNEL OF WEB CONTENT (Computer systems and information technologies, 2022)
Research conducted over the past ten years in the field of search engine optimization on the Internet shows the creation of a new phenomenon - virtual promotion [1]. Its main goal is to increase the level of sales of goods through technologies that exist in virtual space. In terms of properties, virtual promotion is similar to a logistics channel, but with the characteristics of a marketing channel. That is, virtual promotion can be described as the establishment of a channel for the transmission of a special message from the company to a potential buyer of its goods or services. This article proposes to consider the problem of creating and managing such a message in cyberspace. To do this, it is proposed to solve the problem of situational management of the semantic kernel of web content. At the first stage the review of properties of a semantic kernel is carried out. This analysis allows us to formulate the problem of situational management of the semantic kernel. The main idea of ​​this problem is that the current situation is a variant of the semantic kernel of web content. Then the paper proposes a mathematical model for estimating the current situation and choosing the target situation. Conditions are also proposed to determine the need for transition between situations. The article also describes the algorithmic support for the implementation of the method of solving the problem of situational management. The result of the algorithm is K-applicant, ie the semantic kernel that describes the class of needs, which was identified at the stage of clustering. The prospect for further research is the software implementation of this algorithm on the NodeJS platform.
Keywords: Virtual promotion of a product; situational management; semantic kernel; web content